OsNPR1 negatively regulates herbivore‐induced JA and ethylene signaling and plant resistance to a chewing herbivore in rice. Issue 3 (12th July 2012) - Li, Ran; Afsheen, Sumera; Xin, Zhaojun; Han, Xiu; Lou, Yonggen
<x xml:space="preserve">Abstract</x> NPR1 (a non‐expressor of pathogenesis‐related genes1) has been reported to play an important role in plant defense by regulating signaling pathways. However, little to nothing is known about its function in herbivore‐induced defense in monocot plants. Here, using suppressive substrate hybridization, we identified a NPR1 gene from rice, OsNPR1, and found that its expression levels were upregulated in response to infestation by the rice striped stem borer (SSB) Chilo suppressalis and rice leaf folder (LF) Cnaphalocrocis medinalis, and to mechanical wounding and treatment with jasmonic acid (JA) and salicylic acid (SA). Moreover, mechanical wounding induced the expression of OsNPR1 quickly, whereas herbivore infestation induced the gene more slowly. The antisense expression of OsNPR1 (as‐npr1), which reduced the expression of the gene by 50%, increased elicited levels of JA and ethylene (ET) as well as of expression of a lipoxygenase gene OsHI‐LOX and an ACC synthase gene OsACS2. The enhanced JA and ET signaling in as‐npr1 plants increased the levels of herbivore‐induced trypsin proteinase inhibitors (TrypPIs) and volatiles, and reduced the performance of SSB. Our results suggest that OsNPR1 is an early responding gene in herbivore‐induced defense and that plants can use it to activate a specific and appropriate defense response against invaders by modulating signaling pathways.